2023
DOI: 10.1111/jfb.15417
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic life‐history signatures are retained in modern and ancient Atlantic bluefin tuna vertebrae

Abstract: Isotopic, tagging and diet studies of modern-day teleosts lacked the ability to contextualise life-history and trophic dynamics with a historical perspective, when exploitation rates were lower and climatic conditions differed. Isotopic analysis of vertebrae, the most plentiful hard-part in archaeological and museum collections, can potentially fill this data-gap. Chemical signatures of habitat and diet use during growth are retained by vertebrae during bone formation. Nonetheless, to fulfil their potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Since BFT bone is likely to record multiple years of foraging behaviour (Andrews et al, 2023), the observed significantly different Black Sea isotope values and low NE Atlantic and Mediterranean overlap proportions suggest that most Black Sea BFT migrated consistently to–or were resident in–this region over multiple years for foraging while NE Atlantic and Mediterranean BFT seldomly used this region as a foraging habitat. Indeed, high‐site fidelity has been reported in BFT (Block et al, 2005; Cermeño et al, 2015) but our findings would go further, supporting tagging data (De Metrio et al, 2004) to suggest that current Atlantic foraging behaviours are probably not characteristic of all BFT, even at large body size (Rouyer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since BFT bone is likely to record multiple years of foraging behaviour (Andrews et al, 2023), the observed significantly different Black Sea isotope values and low NE Atlantic and Mediterranean overlap proportions suggest that most Black Sea BFT migrated consistently to–or were resident in–this region over multiple years for foraging while NE Atlantic and Mediterranean BFT seldomly used this region as a foraging habitat. Indeed, high‐site fidelity has been reported in BFT (Block et al, 2005; Cermeño et al, 2015) but our findings would go further, supporting tagging data (De Metrio et al, 2004) to suggest that current Atlantic foraging behaviours are probably not characteristic of all BFT, even at large body size (Rouyer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Isotope signatures from multiple years prior to catch are retained across the growth axes of BFT vertebrae (Andrews et al, 2023). Therefore, to obtain averages of foraging across seasons and avoid overrepresenting potential sporadic seasonal changes or foraging behaviours, we aimed to (1) sample the same element (vertebrae), whenever possible, and (2) represent roughly equal portions of acellular (cortical) and cellular (spongy) bone across the growth‐axis, between samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations